Defining the intrinsically disordered C-terminal domain of SSB reveals DNA-mediated compaction - Green, Matthew; Hatter, Louise; Brookes, Emre; Soultanas, Panos; Scott, David J. (Elsevier, 2016)
The bacterial single-stranded DNA (ssDNA) binding protein SSB is a strictly conserved and essential protein involved in diverse functions of DNA metabolism, including replication and repair. SSB comprises a well-characterized tetrameric core of N-terminal oligonucleotide binding OB folds that bind ssDNA and four intrinsically disordered C-terminal domains of unknown structure that interact with partner proteins. The generally accepted, albeit speculative, mechanistic model in the field postulates that binding of ssDNA to the OB core induces the flexible, undefined C-terminal arms to expand outwards encouraging functional interactions with partner proteins. In this structural study, we show that the opposite is true. Combined small-angle scattering with X-rays and neutrons coupled to coarse-grained modeling reveal that the intrinsically disordered C-terminal arms are relatively collapsed around the tetrameric OB core and collapse further upon ssDNA binding. This implies a mechanism of action, in which the disordered C-terminal domain collapse traps the ssDNA and pulls functional partners onto the ssDNA.